2006
DOI: 10.1002/da.20153
|View full text |Cite
|
Sign up to set email alerts
|

An open trial of paroxetine for the “offensive subtype” oftaijin kyofusho and social anxiety disorder

Abstract: The taijin kyofusho (TKS) offensive subtype is thought to be a culture-bound syndrome similar to social anxiety disorder (SAD). In Western countries, such patients would be diagnosed as having delusional disorder, somatic subtype, or body dysmorphic disorder. Recently, open trials for the TKS offensive subtype and a randomized controlled trial for body dysmorphic disorder demonstrated that selective serotonin reuptake inhibitors (SSRIs) might be as effective in TKS as in SAD. This study investigated the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
1
34
1
2
Order By: Relevance
“…[84,86] Similar to most clinical studies of SAD, [80] more males than females-about 3:2 ratio-present with TKS in Japanese clinical settings. [84] In addition, TKS appears to respond well to an SSRI [85,87] or an SNRI. [88] The relationship between SAD and the offensive subtype of TKS has been examined in several studies.…”
Section: Fear Of Humiliation or Embarrassmentmentioning
confidence: 99%
“…[84,86] Similar to most clinical studies of SAD, [80] more males than females-about 3:2 ratio-present with TKS in Japanese clinical settings. [84] In addition, TKS appears to respond well to an SSRI [85,87] or an SNRI. [88] The relationship between SAD and the offensive subtype of TKS has been examined in several studies.…”
Section: Fear Of Humiliation or Embarrassmentmentioning
confidence: 99%
“…A chart review of 48 patients with c-TK reported a 48% response rate to treatment with clomipramine or fluvoxamine [26]; an open-label trial reported that 6 of 11 patients diagnosed with c-TK responded to milnacipran [27], and a recent open-label trial reported that 41% of 19 patients diagnosed with c-TK responded to paroxetine [28]. These preliminary SSRIs and SNRI studies only used the CGI-Global Improvement Scale and/or the Taijin-Kyofu-Sho offensive anxiety scale (0-3 points), the validity of which was not examined systematically for the evaluation of c-TK symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on the efficacy of SSRIs and SNRI for BDD and the delusional variant of BDD (delusional disorder, somatic type) [22,23,24,25]. In addition, preliminary studies [12,26,27,28] suggest that SSRIs and SNRI may be effective for the treatment of c-TK. Given the suggestion of consistent pharmacologic responsiveness for SAD, BDD, and c-TK, it may be worth expanding the current DSM diagnostic criteria for SAD to incorporate symptoms of c-TK.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the diagnostic criteria for psychotic disorders and/or body dysmorphic disorder in the DSM-IV could be modified to diagnose such patients with high reliability. Nevertheless, there are some case reports and case series reports that suggest that selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) are more effective for conviction subtype TK than antipsychotics (Clarvit et al, 1996;Matsunaga et al, 2001;Nagata et al, 2003;Nagata et al, 2006;Nagata et al, 2005). Our own experiences with six cases of offensive subtype SAD also suggest that they respond to the CBT program as well as those without offensive fears (Chen et al, submitted, Group cognitive-behavior therapy for Japanese patients with social anxiety disorder: Outcomes and their predictors).…”
Section: Therapeutic Implications Of Expanding Diagnostic Criteria Fomentioning
confidence: 99%
“…It is possible that many clinicians in the West are diagnosing patients with conviction subtype TK as conditions other than SAD, including delusional disorder, body dysmorphic disorder or paranoid disorder, since the diagnostic criteria for SAD in DSM-IV and ICD-10 do not fully cover conviction subtype TK (Kasahara, 2005;Lochner et al, 2003;TanakaMatsumi, 1979). Importantly, there are some single case reports and case series reports that suggest that selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) are more effective for conviction subtype TK than antipsychotics (Clarvit et al, 1996;Matsunaga et al, 2001;Nagata et al, 2003;Nagata et al, 2006;Nagata et al, 2005).…”
Section: Introductionmentioning
confidence: 99%